Effects of Treated Fritted Dental Porcelain Particles on the Fracture Toughness and Surface Hardness of Poly Methylmethacrylate as Denture Base - Saad Alsharif; Asam Abudalazez; Zainal Arifin Ahmad (Khalij-Libya Journal of Dental and Medical Research, 2024)
This research aimed to assess the fracture toughness and surface hardness properties of polymethyl methacrylate (PMMA) reinforced with fritted dental porcelain (FDP) particles at various weight percentage levels. Eighty specimens were prepared and divided into four groups. The PMMA matrix was the control group, with others having 5, 10, and 15 wt.% FDP particles. The three-point bending test was carried out to determine fracture toughness (KIC). The surfaces of the fractured specimens were subsequently examined using a Field Emission Scanning Electron Microscope (FESEM). Additionally, the surface hardness of the specimens was assessed through the Vickers hardness (VH) test. The results indicate that the KIC value of FDP/PMMA composite slightly decreased as FDP particles containing increased. The surfaces of the PMMA matrix specimens exhibit a smooth appearance, whereas the FDP/PMMA composite containing 5 wt.% FDP particles displays a rougher surface and FDP particles appearing partially embedded and adhered to the PMMA matrix. With an increase in amount of FDP particles increases from 10 to 15 wt.%, a tendency for particle agglomeration is observed, suggesting that the particles are not fully wetted by the PMMA matrix. The FDP/PMMA composite with different FDP particle concentrations had greater hardness than the PMMA matrix. The optimal results were observed at 5 wt.% FDP particles. يهدف هذا البحث إلى تقييم تحمل الكسر وخصائص صلابة سطح البولي ميثيل ميثاكريلات (بى إم إم أى) المعززة بجزيئات البورسلين السني الدقيقة (إف دى بى) بمستويات نسب وزنية مختلفة. تم تحضير ثمانين عينة وتقسيمها إلى أربع مجموعات. كان راتنج بى إم إم أى هو المجموعة الضابطة، بينما كانت المجموعات الأخرى تحتوي على 5 و10 و15% بالوزن من جزيئات إف دى بى. تم إجراء إختبار الإنحناء ثلاثي النقاط لتحديد صلابة الكسر (كى أى سي). تم بعد ذلك فحص أسطح العينات المكسورة باستخدام مجهر المسح الإلكتروني (إف إي إس إي إم). بالإضافة إلى ذلك ، تم تقييم صلابة سطح العينات من خلال اختبار صلابة فيكرز (فى إتش). تشير النتائج إلى أن قيمة كى أى سى لمركب إف دى بى/ بى إم إم أى إنخفضت قليلا كلما زادت كمية جزيئاتت إف دى بى. أظهرت أسطح عينات راتنج بى إم إم أى مظهر أملس، في حين أن مركب إف دى بى/ بى إم إم أى الذي يحتوي على 5 بالوزن.٪ جزيئات إف دى بى أظهر سطح أكثر خشونة وظهرت جزيئات إف دى بى جزئيا منغرسة وملتصقة في راتنج بى إم إم أى. مع زيادة كمية جزيئات إف دى بى من 10 إلى 15 بالوزن.٪، لوحظ ميل لتكتل للجزيئات، مما يشير إلى أن الجزيئات لا يتم ترطيبها بالكامل بواسطة راتنج بى إم إم أى. كان لمركب إف دى بى/ بى إم إم أى بتركيزات جزيئات إف دى بى المختلفة صلابة أكبر من راتنج بى إم إم أى. وقد لوحظت النتائج المثلى عند نسبة 5٪ بالوزن من جزيئات إف دى بى